Agreement between routine and research measurement of infant height and weight. Issue 1 (29th September 2014) - Bryant, M; Santorelli, G; Fairley, L; Petherick, E S; Bhopal, R; Lawlor, D A; Tilling, K; Howe, L D; Farrar, D; Cameron, N; Mohammed, M; Wright, J
Abstract : In many countries, routine data relating to growth of infants are collected as a means of tracking health and illness up to school age. These have potential to be used in research. For health monitoring and research, data should be accurate and reliable. This study aimed to determine the agreement between length/height and weight measurements from routine infant records and researcher-collected data. Methods: Height/length and weight at ages 6, 12 and 24 months from the longitudinal UK birth cohort (born in Bradford; n=836–1280) were compared with routine data collected by health visitors within 2 months of the research data (n=104–573 for different comparisons). Data were age adjusted and compared using Bland Altman plots. Results: There was agreement between data sources, albeit weaker for height than for weight. Routine data tended to underestimate length/height at 6 months (0.5 cm (95% CI −4.0 to 4.9)) and overestimate it at 12 (−0.3 cm (95% CI −0.5 to 4.0)) and 24 months (0.3 cm (95% CI −4.0 to 3.4)). Routine data slightly overestimated weight at all three ages (range −0.04 kg (95% CI −1.2 to 0.9) to −0.04 (95% CI −0.7 to 0.6)). Limits of agreement were wide, particularly for height. Differences were generally random, although routine data tended to underestimate length in taller infants and underestimate weight in lighter infants. Conclusions: Routine data can provide an accurate and feasible method of data collection for research, though wide limits of agreement between data sources may be observed. Differences could be due to methodological issues; but may relate to variability in clinical practice. Continued provision of appropriate training and assessment is essential for health professionals responsible for collecting routine data.